Analisis Implementasi Manajemen Budaya Kesehatan Lingkungan Di Pondok Pesantren Daruttakwien Bekasi - El-Ghifary, Muhammad Ghufron; Erislan, Erislan; Irianto, Hari Eko (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to measure the implementation of environmental health management with statistic descriptive of qualitative that analyzes the Implementation of Environmental Health Culture Management at the Daruttakwien Bekasi Islamic Boarding School. The research sample consisted of 39 daily managers who lived at the Daruttakwien Bekasi Islamic boarding school. using the total sampling illustration method. Information was collected using a Likert scale questionnaire. The research results from each dimension of environmental health culture show an average value of 43.62 (87%) in the personal dimension in the very good category, from the behavioral dimension it displays an average value of 39.36 (79%) in the good category, in the organizational dimension a value is obtained. an average of 40.21 (80%) was categorized as good. With respect to the human component of the teamwork evaluation, the K3 parts of the K3 management assessment for environmental health culture implementation yielded very excellent findings (528), as did the training assessment (160), and the assessment from reporting (160). (502), the work environment Islamic boarding school administrators received a very good category (511). In the behavioral dimension, the compliance aspect received a fairly good category (775), the aspect of using cleaning equipment received a score in the quite good category (447), and the communication aspect received a very good category (313). In the organizational dimension, the regulatory aspect received a good category (787), leadership received a good category (631), risk received a fairly good category (150) under the excellent heading. Based on data collected from three different angles, it was determined that Daruttakwien Bekasi Islamic Boarding School exhibited an environmental health culture level 1 (emerging) application of environmental health management. This was supported by a total score of 1.01. It is hoped that the results of this research can be used as data for Islamic boarding schools to improve environmental health management in Islamic boarding schools' environmental health culture so that they can improve the health quality of students and all boarding school residents.